Light Microscopic Examination of Uterus in Pinealectomized Rats - Pekmez, Hıdır; Kuş, İlter; Çolakoğlu, Neriman; Ögetürk, Murat; Kuloğlu, Tuncay; Sarsılmaz, Mustafa (Fırat University, 2005)
Objectives: The aim of this study was to investigate the histological changes in uterus tissue of rats after pinealectomy at light microscopic level Materials and Methods: For this purpose, 14 female Wistar-Albino rats were divided equally into two groups. Rats in group I were used as control (sham-pinealectomy), whereas rats in group II were pinealectomized. At the end of the one-month experimental period, all rats were killed by vascular perfusion. Uteri of all rats were weighed. Following routine histological procedures, uterus tissue specimens were examined under a light microscope. Results: In the pinealectomized rats, there were increases in uterus weights. In light microscopic examination, it was observed that increase in endometrial connective tissue cells and dilatation in endometrial glands after pinealectomy. Additionally, myometrial blood vessels were filled as compared to control group. Conclusion: Endometrial hyperplasia which appeared to be linked with the decrease in melatonin's antigonadal activity due to the lack of melatonin was seen in experimental rats after surgical removal of the pineal gland. ©2005, Fırat Üniversitesi, Tıp Fakültesi

Amaç: Bu çalışmada, pinealektomi sonrası uterusta meydana gelen histolojik değişikliklerin ışık mikroskop düzeyde incelenmesi amaçlandı. Gereç ve Yöntem: 14 adet Wistar-Albino cinsi dişi sıçan iki eşit gruba ayrıldı. Grup I'deki sıçanlar kontrol (sham-pinealektomi) olarak kullanıldı. Grup II'deki sıçanlara ise pinealektomi yapıldı. Bir aylık deney süresi sonunda sıçanlar vasküler perfüzyonla öldürüldü. Bütün hayvanlardan alınan uteruslar tartıldı. Daha sonra, uterus doku örnekleri rutin histolojik prosedürleri takiben ışık mikroskobunda incelendi. Bulgular: Pinealektomili sıçanlara ait uterus ağırlıklarında bir artışın meydana geldiği tespit edildi. Işık mikroskobik incelemelerde ise, pinealektomi sonrası endometriyum bağ dokusu hücrelerinde artış, endometriyal bezlerde dilatasyon gözlendi. Ayrıca, miyometriyum tabakasındaki kan damarları da kontrol grubuna oranla daha dolgundu. Sonuç: Deneysel olarak pineal bezleri çıkarılmış sıçanlarda, melatonin hormonunun azalması ile paralel ortaya çıkan antigonadal aktivitesindeki gerilemeye bağlı olduğu düşünülen endometriyal hiperplazi belirlendi. ©2005, Fırat Üniversitesi, Tıp Fakültesi
Pinealektomili Sıçanlarda Uterusun Işık Mikroskop Düzeyde İncelenmesi